Sustainability evaluation of a medium scale GSHP system in a layered alluvial setting using 3D modeling suite. (January 2016) - Perego, R.; Guandalini, R.; Fumagalli, L.; Aghib, F.S.; De Biase, L.; Bonomi, T.
Graphical abstract: Highlights: Sustainability evaluation of a vertical closed-loop GSHP system is performed. A newly developed modelling suite is validated for low enthalpy simulations. Effects of main subsurface and design parameters are studied. Interference is amplified by strong heterogeneity of Po Plain alluvial deposits. Homogeneous model assumption underrates the magnitude of thermal imbalance issues. Abstract: In this study the effects on the thermal field of a medium scale GSHP system located in Alessandria (Italy) and installed in highly heterogeneous alluvials are considered. The system was monitored over a year and data showed a progressive loss of efficiency. Simulation results obtained from a 3D numerical model show that the analyzed GSHP system has an inadequate design even for a short/medium period operation. A strong probe interference phenomenon was observed, due to the particular layout of the probe field and to the high energy request for building conditioning. The efficiency loss is also amplified by the presence of alluvial deposits with poor thermal properties. Adopting a homogeneous distribution of the thermal properties of the subsurface results in an underestimation of the thermal alteration of 25% while the increase of probe distance by 55% produces a reduction of thermal alteration of 45%. In this case study the homogeneous subsurface assumption leads to excessive simplification of the observed strong heterogeneity and it underrates thermal impact on the soil, especially in layers with poor thermal properties.